Efficacy and safety of a new vaginal gel for the treatment of symptoms associated with vulvovaginal atrophy in postmenopausal women: A double-blind randomized placebo-controlled study. (May 2021) - De Seta, Francesco; Caruso, Salvatore; Di Lorenzo, Giovanni; Romano, Federico; Mirandola, Mariateresa; Nappi, Rossella E.
Highlights: More than 50% of menopausal women suffer from vulvo-vaginal atrophy. Estrogen therapy has been used for the management of symptoms of vulvo-vaginal atrophy. Meclon Idra Alfasigma is a new natural vaginal gel. The new gel was shown in this study to be effective, tolerable and safe. Study participants confirmed that the new gel reduced both symptoms of vulvo-vaginal atrophy and sexual impairment. Abstract: Objective: The aim of the present randomized placebo-controlled single-center study was to assess the efficacy and safety of a new vaginal gel (Meclon Idra - Alfasigma) in the treatment of vulvovaginal atrophy (VVA). The gel is composed of sea buckthorn ( Hippophaë rhamnoides ) oil, aloe vera, 18β-glycyrrhetic acid, hyaluronic acid and glycogen. The study assessed whether the gel can reduce VVA symptoms (vaginal dryness, itching, burning sensation) and improve sexual function in postmenopausal women over 12 weeks. Study Design: Postmenopausal women (n° = 60 ) reporting VVA symptoms were recruited and randomized in a 1:1 ratio to the gel or placebo. Active vaginal gel or placebo was applied for 14 days and then twice a week for 90 consecutive days. Main outcome measure: The Vaginal Health Index (VHI), including vaginal pH, was used to assess changes in objective signs, whereas the self-reported Female Sexual Function Index (FSFI) was used to investigate sexual function. Results: Meclon Idra was effective in reducing vaginal pain, dyspareunia and vaginal pH, with the VHI showing significant improvement at day 90 (P < .0001), and in reducing each VVA symptom (vaginal dryness, vaginal itching, burning sensation) at weeks 2 and 4, and the end of the study (P < .0001). The analysis of FSFI scores showed, after the end of treatment, an improvement of sexual function in the active-treatment group, with a statistically significant increase (P < 0.001) in all domains scores and total score (P < 0.001). Conclusions: The present single-center randomized clinical trial demonstrated the efficacy, tolerability and safety of 12-week treatment with a new vaginal gel in postmenopausal women with symptoms associated with VVA. Based on this trial, the gel seems to be a valid choice as a single, local agent for relieving VVA symptoms and improving sexual function, and to have good compliance. This trial is registered prospectively with the Clinical Trials Registry – India, number CTRI/2019/05/01911.